Management control in exploitation, exploration and organizational ambidexterity – The use and formalization of management control systems as antecedents for different modes of innovation - Manneri, Ville (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study examines the relationship between management control and different modes of innovation – exploitation and exploration. Exploitation refers to the refinement of the existing competencies of an organization and relates to the introduction of incremental innovations in order to perform well in today’s competition. In turn, exploration refers to the search of new competencies and relates to the introduction of more radical innovations in order to survive in the competition on the long run. Given that exploitation and exploration represent in many ways conflicting activities in organizations, this study further examines how management control systems influence on the organizational ability to balance contradictory demands within an organization, commonly referred to as organizational ambidexterity. In order to form an in-depth understanding of the research phenomenon, the study followed an action-oriented research approach. The research scope of the study was designed to involve both the different ways in which management control systems are used in organizations as well as the different ways in which employees interpret the formalization of control. For this purpose, the theoretical frameworks of ‘levers of control’ (consisting of belief, boundary, diagnostic and interactive control systems) and different types of control formalization (outlining enabling and coercive forms of bureaucracy) were employed as major theoretical lenses for the study. The empirical part of the study was conducted as a case study within a single organization, Textile. Textile was selected as the research organization for the study based on its large size, maturity of the business and the organization’s strategic pursuit to increase its innovativeness. The empirical data for the study was gathered through semi-structured interviews, participant observations and examination of archival material. The findings of the study contribute to management accounting research by providing empirical evidence that belief systems have an important supportive role in encouraging innovativeness in organizations that focus on exploitative innovation. Additionally, the findings indicate that the dynamic interplay between belief and boundary systems supports exploitative innovation but hinders exploratory innovation by limiting employees’ risk-taking. Moreover, the findings suggest that diagnostic control systems involving features from enabling formalization support exploitative innovation. Finally, the study provides empirically evidence that belief systems and rewarding systems serve as important means to balance tensions that arise from pursuing a strategy which involves ambidextrous elements.